Dynamism at Palestra Green - Scherling, Ian C. (Kansas State University, 2009)
The American campus is a distinct place. Harboring collegial values much different from American social-scapes, urban campuses are insular places of outward-minded activism. The University of Pennsylvania is breaking down these perceived barriers that separate its campus from the city; attempting to reconnect with adjacent neighborhoods, civic institutions and the greater Philadelphia-area. Dynamism at Palestra Green seeks to establish this connection along the most important pedestrian corridor linking Penn to Center City Philadelphia. A proper connection requires extensive knowledge of Penn’s genius loci. By synthesizing an analysis of the historic DNA of Penn and its spaces, as well as regionalism and site-specific programming, the proper design of Palestra Green is achieved. Furthermore, the proposed site design is intended to provide flexible spaces for the accommodation of numerous programmatic functions located both on site and in adjacent campus buildings. Adapting to seasonal campus, event and civic programming while adhering to the aesthetic and underlying qualities of Penn creates a truly unique and dynamic destination. Through this robust design, Palestra Green connects to the whole of Penn, properly accommodates the range of uses and events taking place on site, and contributes to the extensive park network in Philadelphia. In addition, the implementation of multiple designed systems provides a diverse set of amenities contributing to the flexibility of use and sustainability at Palestra Green. Supporting these solutions is a project-specific conceptual framework driven by personal philosophy and experience. The conceptual structure is tuned to actively reconcile and resolve all site and program issues. In its final state, Dynamism at Palestra Green communicates the significance of all proposed components, discusses the space’s long-term value to the university and city and exhibits how the new Palestra Green positively contributes to the profession of landscape architecture.
Keywords: Collegiate Campus Design; Spatial Flexibility; Systems; Landscape Program; University of Pennsylvania; Connectivity; Landscape Architecture (0390)